IMPLEMENTASI PERATURAN DAERAH NOMOR 5 TAHUN 2010 TENTANG PENGELOLAAN DAN PENGUSAHAAN SARANG BURUNG WALET DI KECAMATAN SAMBAS KABUPATEN SAMBAS - Hidayati E.01108013, Luthfi (FISIP Universitas Tanjungpura, 2013)
This journal research is intended to provide oversight and guidance to employers on the management and operation of swallow bird's nest. The issues concerning to the management and operation of swallow bird nest is quite interesting to study because there are many transfer functions of the store building (shop) into swallow breeding. This thesis also aimed to determine the factors that influence the implementation of local regulations No. 5 year 2010 concerning the management and operation of swallow birdâ€™s nest insub-Sambas Sambas Regency which has not been optimal. The research was done by conducting interviews with informants consisting of 4 (four) people. In implementing this policy, there are four factors that influence it in accordance with the theory of George C.Edward III i.e., communication, resources, disposition, and bureaucratic structures.Â Keywords: implementation management Swallow birdâ€™s nest